Historis Boarding School Serta Faktor – Faktor Yang Mempengaruhinya - Rahmatullah Akbar; Karoma Karoma; Mardiah Astuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education is a process of giving humans various kinds of situations that aim to empower themselves. One type of education in Indonesia is boarding school. Boarding school is an educational institution that provides a place to live for students. Boarding School has a history at the beginning of its formation. In the process of developing a boarding school there are influencing factors. In addition to mapping the factors that influence the development of boarding schools, this paper also discusses their strengths and weaknesses. This paper is based on data collected through library research. The results of the study show that there is a historical background behind the formation of boarding schools, showing several factors that influence the development of boarding schools, and the advantages and disadvantages of boarding schools. This paper suggests the need to expand the cases studied, and discuss more comprehensive data sources.